Indirectly additive manufactured deformable bladder model for a pelvic radiotherapy phantom (Transactions on Additive Manufacturing Meets Medicine, 2021)
The increasing variance in imaging radiotherapy demands the use of deformable phantoms for validation or quality assurance as well as for general training. This paper describes the development and manufacturing of a deformable urinary bladder model that can be implemented in a radiotherapy pelvic phantom. The advantages of additive manufacturing (AM) are used to produce an anatomically realistic mold, as well as a dissolvable core. The casted silicon bladder has different wall thicknesses which show realistic deformation behavior compared to a human bladder.
Keywords: Phantom; radiotherapy; indirect additive manufacturing